KESALAHAN PENGUTIPAN PADA SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS NIAS RAYA TAHUN 2022 - Hia, Suarni (Universitas Nias Raya, 2025)
The background of the problem in this study is that there are several writing errors, including errors in writing citations. The purpose of this study is to describe the misquotation in the 2022 student thesis of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, University of Nias Raya. This type of research is a type of qualitative research with a descriptive approach. The results of the study found that there were 2 citation errors in writing a thesis, namely direct citation errors as many as 8 errors that did not put quotation marks on sentences. And indirect quoting errors for students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, University of Nias Raya as many as 7 errors that do not give signs in parentheses and space 1 (one). Through this research it is recommended to; Students to increase curiosity about Indonesian learning because it is related to everyday life. Lecturers to always remind, provide motivation, and direction to students to study seriously so that they are able to use good and correct quotes, both orally and in writing; 3) Nias Raya University library so that it can facilitate students to be able to study optimally.